GERAKAN LITERASI DIGITAL PELAJAR NAHDLATUL ULAMA - Syahputra, Muhammad Candra (Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
The development of the world of information and communication technology we cannot avoid, this creates a wide open information space. However, the negative impacts of information and communication technology should also be wary of us, such as spreading false news, radical understanding and information that is driven by the interests of groups. Therefore, the need to create human resources who have digital literacy understanding. This research uses qualitative approach and is a field research, while data obtained through interviews and pbservations in the field. Nahdlatul ulama students who are members of the PC IPNU and PC IPPNU Bandar Lampung City aware of it so as to carry out digital literacy movements through activities such as pesantren journalism, social media management, design schools, and online studies which is carried out systematically on an annual basis in order to realize human beings who are responsible for utilizing digital media so as to create information that is accurate, trustworthy, soothing, does not cause anxiety, and disunity.